A study on the appraisal practices of selected archives of government institutions in Metro Manila - Odilao, Angeline May I.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
The study was conducted to know how appraisal is done in archives of government institutions in Metro Manila. It focused on appraisal practices in six selected archives which include the Legislative Records and Archives Service of the Senate of the Philippines (LRAS), Cultural Center of the Philippines Library and Archives (CCPLA), National Historical Institute Resource Center (NHIRC), Intramuros Administration's Father Luis Merino Library (FLM), Legislative Archives Service of House of Representatives (LAS), and The National Archives of the Philippines (NAP). The study was conducted to identify their overall mission/objectives; determine the criteria employed by archivists in appraisal; identify the external factors that affect the process; know the similarities and differences among the institutions when it comes to appraisal; and know the profile of the archivists or the personnel in charge of the archives.
The data gathered from the survey questionnaire and interview revealed that: (a) half of the archives are repositories of records of parent institution while the other half focused on collecting materials related to arts, culture or Philippine history; (b) all respondents have mission statements and four out of six have appraisal policies; (c) four of the respondents are heads of a particular division/bureau/section while two are personnel assigned to do other tasks; (d) no respondent applies all the criteria in appraisal and the degree of importance given to a criteria by each respondent differs from the other; (e) the element that is always considered by all the respondents is the administrative value of records while the elements that are least considered are the authority/influence of other parties and the cost of records retrieval; (f) among the three modules, values-of-information ranked the highest while cost-of-retention ranked the lowest; (g) in terms of the overall ranking of the types of analysis used in appraisal, content analysis ranked the highest, use and functional analysis come in second and third, while analysis of relation of the record to other documentation ranked the lowest; (h) CCPLA. NHIRC and FLM least applies functional analysis while LRAS, LAS and NAP primarily apply this analysis; (i) four out of six are affected more by internal policies and practices than external relations; (j) external factors are outside researchers, approval and decision making of top management and records disposition schedules of other agencies; (k) five out of six apply the criteria in appraisal with consistency; (1) half of the respondents apply personal values in appraisal; and (m) five out of six respondents think that their appraisal practices reflect Frank Boles' theory.
Recommendations included focusing on the value of records rather than the cost of retaining them, knowing first the overall mission/objectives of the institution before appraising records, formulating an appraisal policy, being consistent in the practice of appraisal, and making appraisal decisions transparent if personal values or other preferences are applied in the process.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Administrative agencies -- Philippines -- Manila Metropolitan Area; Appraisal of archival materials -- Philippines -- Manila Metropolitan Area